Mono- and heterofunctionalized silica magnetic microparticles (SMMPs) as new carriers for immobilization of lipases - de Lima, Lionete Nunes; Vieira, Gustavo Nakamura Alves [UNESP]; Kopp, Willian; Tardioli, Paulo Waldir; Giordano, Raquel L.C. (Elsevier, 2016)
In order to improve economic viability of an enzymatic process, the use of an operationally stable and low-cost biocatalyst is encouraged. Although the immobilization of lipases is widely reported, the search for new supports and immobilization protocols with better properties is still important. In this study, mono- and heterofunctionalized silica magnetic microparticles (SMMPs) were synthetized for immobilization of lipase B from Candida antarctica (CALB). The SMMPs were prepared in a micro-emulsion system containing sodium silicate and superparamagnetic iron oxide nanoparticles, followed by chemical modification with octyl groups and octyl plus aldehyde groups. These supports allowed the immobilization of CALB by hydrophobic adsorption or hydrophobic/covalent linkages, achieving immobilization yield of 88% and recovered activities of 128% and 59%, respectively. The performance of the magnetic biocatalysts was evaluated in the synthesis of xylose fatty acid esters (laurate or oleate) in tert-butyl alcohol medium, yielding around 60% conversion after 48 h under optimized conditions (xylose/fatty acid molar ratio of 1:0.2, 55 °C, and activity load of 37.5 U/g). The magnetic biocatalyst was used in 10 reaction cycles of 48 h at 46 °C maintaining high xylose conversions. Besides, the biocatalyst might be easily and quickly recovered from the reaction medium by an external magnetic field, an operational advantage in the case of viscous and complex media, e.g., medium containing insoluble sugars and molecular sieves.
Keywords: Candida antarctica lipase B; Heterofunctionalization; Silica magnetic microparticles; Xylose fatty acid ester